Can Gender and Motion Sickness Susceptibility Predict Cybersickness in VR ? - Pohlmann, Katharina M. T.; Li, Gang; McGill, Mark; Pollick, Frank; Brewster, Stephen (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
VR headsets are becoming part of our everyday lives, however, cy-bersickness is a common side effect when using these devices. The experience and intensity of symptoms varies greatly between indi-viduals with some seemingly resistant to cybersickness and other suffering greatly. It is still not clear why some individuals suffer more than others and what characteristics might contribute to such a resistance. In this study, we investigate two individual characteris-tics that have been commonly discussed in relation to cybersickness with no clear consensus being established so far: gender and motion sickness history. Findings support the notion that females are more susceptible to motion sickness. However, one's motion sickness history did not relate to symptoms of cybersickness. In line with this, the difference in motion sickness history between genders did not translate to their experience of cybersickness, with males and females experiencing similar levels of cybersickness. These findings demonstrate the complexity of the relationship between gender and motion sickness history and their impacts on the experience of cybersickness. This work highlights the need for future explo-ration of individual characteristics and their effects on cybersickness susceptibility.